A Model-Assisted Approach for Finding Coding Errors in Manual Coding of Open-Ended Questions. (3rd August 2021) - He, Zhoushanyue; Schonlau, Matthias
Abstract: Text answers to open-ended questions are typically manually coded into one of several codes. Usually, a random subset of text answers is double-coded to assess intercoder reliability, but most of the data remain single-coded. Any disagreement between the two coders points to an error by one of the coders. When the budget allows double coding additional text answers, we propose employing statistical learning models to predict which single-coded answers have a high risk of a coding error. Specifically, we train a model on the double-coded random subset and predict the probability that the single-coded codes are correct. Then, text answers with the highest risk are double-coded to verify. In experiments with three data sets, we found that this method identifies two to three times as many coding errors in the additional text answers as compared to random guessing, on average. We conclude that this method is preferred if the budget permits additional double-coding. When there are a lot of intercoder disagreements, the benefit can be substantial.